2016
DOI: 10.1371/journal.pone.0167308
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of the ‘One4All’ HIV Linkage Intervention in Guangxi Zhuang Autonomous Region, China

Abstract: BackgroundIn Guangxi Zhuang Autonomous Region, China, an estimated 80% of newly-identified antiretroviral therapy (ART)-eligible patients are not engaged in ART. Delayed ART uptake ultimately translates into high rates of HIV morbidity, mortality, and transmission. To enhance HIV testing receipt and subsequent treatment uptake in Guangxi, the Chinese Center for Disease Control and Prevention (CDC) executed a cluster-randomized trial to assess the effectiveness and cost-effectiveness of a streamlined HIV testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
2
7
0
Order By: Relevance
“…We adapted and extended a previously published HIV dynamic transmission model that was used to estimate the health benefits and costs of HIV prevention and treatment interventions in the United States [12][13][14] ; British Columbia, Canada [15][16][17] ; and Guangxi province, China. 18 We modified the compartmental model both to accommodate the distinctive features in HIV microepidemics across US cities 4 and to allow for assessment of a range of HIV treatment and prevention interventions to be evaluated jointly in future applications. For each demonstration city, the adult population aged 15 to 64 years was partitioned into compartments on the basis of biological sex, race/ethnicity (black/ African American [black], Hispanic/Latino [Hispanic], and non-Hispanic white/others [white]), and HIV risk behavior type (MSM, people who inject drugs [PWID], MSM-PWID, and heterosexual [HET]).…”
Section: Model Descriptionmentioning
confidence: 99%
“…We adapted and extended a previously published HIV dynamic transmission model that was used to estimate the health benefits and costs of HIV prevention and treatment interventions in the United States [12][13][14] ; British Columbia, Canada [15][16][17] ; and Guangxi province, China. 18 We modified the compartmental model both to accommodate the distinctive features in HIV microepidemics across US cities 4 and to allow for assessment of a range of HIV treatment and prevention interventions to be evaluated jointly in future applications. For each demonstration city, the adult population aged 15 to 64 years was partitioned into compartments on the basis of biological sex, race/ethnicity (black/ African American [black], Hispanic/Latino [Hispanic], and non-Hispanic white/others [white]), and HIV risk behavior type (MSM, people who inject drugs [PWID], MSM-PWID, and heterosexual [HET]).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Guangxi Zhuang Autonomous Region, a province in western China, has the second highest HIV-infected reported cases in China, with more than 100 000 reported HIV/AIDS cases by the end of 2016,16 which accounting for ~13% of total national HIV/AIDS cases. Guigang city is a prefecture-level city in Guangxi, and there were more than 5000 reported HIV/AIDS cases during 2008–2013, which listed in the top five among all cities in Guangxi 17.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,25 Taken together with clinical trial results showing benefit to treating all people with HIV regardless of CD4 count or clinical stage, 26,27 our results strongly suggest that a change in approach to provision of treatment for HIV is warranted. Moreover, a study published during the preparation of our manuscript 28 found that the One4All strategy was highly cost-effective, and remained so when tested under various scenarios related to changes in the HIV epidemic over time.…”
Section: Discussionmentioning
confidence: 88%